2016
DOI: 10.1038/jp.2016.96
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of direct fluorescent in buffy coat in the diagnosis of Candida sepsis in neonates

Abstract: The direct fluorescent assay in buffy coat might be useful to support early and accurate diagnosis of CS in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent years, fluorescence staining has attracted more attention due to its potential for rapid diagnosis of fungal infections. Accumulated evidence has shown that fluorescence staining has good diagnostic efficacy in diagnosis of tinea unguium, tinea pedis, tinea capitis, corneal fungal infection and deep fungal infections (Chen et al, ; He et al, ; Higareda‐Almaraz et al, ). The mechanism involves binding of fluorescent dyes, including calcofluor white (CFW), fluorescein isothiocyanate (FITC) and acridine orange (AO), among others (Chick & Behar, ; Moussa, Tayel, & Al‐Turki, ; Sanketh, Patil, & Rao, ), to cellulose or chitin in the cell wall of the fungal through a chemical bond (Roncero & Duran, ; Roncero, Valdivieso, Ribas, & Duran, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, fluorescence staining has attracted more attention due to its potential for rapid diagnosis of fungal infections. Accumulated evidence has shown that fluorescence staining has good diagnostic efficacy in diagnosis of tinea unguium, tinea pedis, tinea capitis, corneal fungal infection and deep fungal infections (Chen et al, ; He et al, ; Higareda‐Almaraz et al, ). The mechanism involves binding of fluorescent dyes, including calcofluor white (CFW), fluorescein isothiocyanate (FITC) and acridine orange (AO), among others (Chick & Behar, ; Moussa, Tayel, & Al‐Turki, ; Sanketh, Patil, & Rao, ), to cellulose or chitin in the cell wall of the fungal through a chemical bond (Roncero & Duran, ; Roncero, Valdivieso, Ribas, & Duran, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has shown that fluorescence staining has good diagnostic efficacy in diagnosis of tinea unguium, tinea pedis, tinea capitis, corneal fungal infection and deep fungal infections (Chen et al, 2016;He et al, 2018;Higareda-Almaraz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%